“REVIVE OR BECOME A SITE” DOCUMENTARY VIDEO OF THE JOURNEY OF MBETEK POTTERY AS AN EDUCATIONAL MEDIA - Aji, Feri Sasmito; Kabelen, Nicholaus Wayong (Universitas Ciputra, 2022)
Malang is a city in East Java. Malang offers not only natural resources as tourist attractions, but also many others, one of which is pottery. Pottery is the art of crafting and shaping clay as desired. Pottery craftsmen who are still active in Malang reside in Pottery Village (Kampung Gerabah). There is a decline in the region’s pottery production center during the crisis. In fact, many pottery businesses went bankrupt; some residents left the profession and searched for new livelihoods. But lately the craftsmen who are still active produce pottery only by order, such as small pots, souvenirs, and wall decorations. The solution offered in this research is a documentary video to educate the audience, since the visual and audio elements of video can convey information such that it can easily be accepted by the audience. The research method used is observation, namely direct observation of the intended location and by conducting interviews with the craftsmen, which were then supported by literature studies sourced from books and journals. The process of designing this documentary video began with pre-production including concepts, storylines, storyboards, and continued with the shooting and editing production stages. The editing stage combined visual and audio elements including text, images, and backsound. Finally, post-production is the process of rendering, whereby all elements are converted into one format, a video form, so that it can be played on several media. Keywords: Pottery, Documentary, Craft, Video, Malang